Peculiarities of Modeling a Specialized Computing System - G. A. Zvonareva; D. S. Buzunov (Статистика и экономика, 2025)
When developing distributed computing systems with parallel data processing, there is a problem of assessing the impact of workload values and structure on its performance indexes. One of the key points in this problem is to assess the impact of various prioritization disciplines on the time characteristics of emerging request queues in the system, for which statistical methods of data analysis are used.The goal of this study is to develop a method for constructing a simulation model that will allow estimating the time characteristics of the system depending on changing workload values and a priorityprocessing algorithm. The method is based on the joint use of the developed simulation model, which describes in detail the functioning of the system of the considered class in time, taking into account conflict situations arising during parallel processing of information, and experimentally obtained individual time characteristics of the system.Materials and methods. The model is implemented in the GPSS language. All stages of applying the presented method are considered. Examples of workload for modeling are given. Justifications for using the presented data, as well as the principles by which they were selected, are given. For the analyzed class of problems, simulation modeling of the computing system was carried out. During the construction of the simulation model of the system a specialized data acquisition device as source of requests; a switch for which a request queue with different priorities is simulated; a data processing device, which is the final recipient of the data were selected as simulation functional nodes.The types of algorithms used to solve the request prioritization problem are taken from common prioritization algorithms typical for the Quality of Service (QoS), used in modern switching equipment. Three prioritization algorithms were considered: without using priorities as a standard; priority queue; Weighted Round Robin as a more complex algorithm.Data on the processing time of various types of requests were obtained experimentally using the Wireshark network traffic analysis tool. The obtained times, as well as the intensity of requests for request processing and the ratio of requests of different types are parameters of the created model and can be changed to simulate another system with a similar architecture.Results. Based on the analysis of the obtained modeling results, the influence of various disciplines for processing request priorities in queues on the system performance indexes is shown. Regenerative model analysis method is used to analyze the obtained data. The obtained method allows for a detailed analysis of the system’s time characteristics, taking into account the prioritization of requests when they are processed in queues.Conclusion. The conducted research analysis shows the impossibility of obtaining these metrics by means of analytical modeling, which emphasizes the novelty of the study. The method obtained during the study is used in the development of systems of the presented class, which emphasizes its practical significance and relevance.